Assessment of Liver Fibrosis With New Modalities - Nichols, Emma Hitt (MD Conference Express, 2015)
Although liver biopsy is considered the gold standard method of assessment for liver fibrosis, it is being displaced by noninvasive testing, such as serum biomarkers, vibration-controlled transient elastography, magnetic resonance elastography, and acoustic radiation force impulse. However, it is important to understand how they perform, particularly in patients with stage 2 to 3 fibrosis.